Myth and fact : Singapore unpacked - Cheong, Jun Rui (Nanyang Technological University, 2022)
In a society shaped by ideals of pragmatism and practicality, there are hidden facets of the everyday that several communities find meaning in and form identities from. These are the powerful rituals and stories that have lived on through the efforts of generations. They form the thread that governs a country’s mindset, foster shared values among a community, and cement identities through comfort in the certainty.